The Perception of Saudi Students toward Using Facilitation Strategies in Digital Classrooms - Althaqafi, Abeer; Salami, Faten Ahmed (Advances in Social Sciences Research Journal, 2021)
Instructors use various strategies to facilitate learning and actively engage students in online courses. In this study, we examined students’ perception of the helpfulness of some different facilitation strategies used by instructors to establish instructors’ presence, instructors’ connection, engagement, and learning in online classrooms. 102 undergraduate students taking online courses due to COVID-19 pandemic at an English language institute at a Saudi university, responded to the web survey. Among the facilitation strategies, instructors being present in the discussion forum rated the highest in two constructs (instructors’ presence and students’ engagement). While video-based instructor introduction rated the highest for instructors’ connectedness. In addition, students found video-based course orientation was the most effective strategy to enhance online learning. Analysis of variance used to detect differences between gender, status, and age on all four constructs measured. No statistically significant differences were noticed for any one of the four latent constructs concerning discipline for the level of education and age. However, there was a significant difference between young and adult learners. Adult students had a stronger perception of using facilitation strategies to establish and enhance the four constructs than young students had.